1976
DOI: 10.1002/1097-4679(197604)32:2<258::aid-jclp2270320211>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of general personality interpretations prior to and after receipt of diagnostic feedback supposedly based on psychological, graphological, and astrological assessment procedures

Abstract: There was no difference in the acceptance of a general personality interpretation supposedly based on psychological, graphological, or astrological assessment procedures. Ss told that their general personality interpretation was based on one of the three assessment procedures, however, accepted the interpretation to a greater degree than did Ss told the interpretation was "generally true of people." S faith in all assessment procedures and perceived diagnostician skill increased significantly from before to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 11 publications
(5 reference statements)
0
20
0
1
Order By: Relevance
“…Subsequent studies have suggested that the relative proportion of positive to negative traits in the description and its perceived source seem important, as well as when they believe that it has been obtained uniquely for themselves (eg. Snyder, Larson, & Bloom, 1976).…”
mentioning
confidence: 98%
“…Subsequent studies have suggested that the relative proportion of positive to negative traits in the description and its perceived source seem important, as well as when they believe that it has been obtained uniquely for themselves (eg. Snyder, Larson, & Bloom, 1976).…”
mentioning
confidence: 98%
“…If this is the case, then such 'creative interpretation' of ambiguous information is reminiscent of the 'Barnum' Effect in which people tend to accept vague and general personality descriptions as being specific to themselves (Forer, 1949;Furnham and Schofield, 1987;Meehl, 1956). Previous research has examined the role of the Barnum Effect in how individuals interpret feedback from psychometric tests, horoscopes, as well as handwriting analysis (Dickson and Kelly, 1985;Fichter and Sunerton, 1983;Synder, Larsen, and Bloom, 1976). However, no previous research has explored the possible role of the Barnum Effect in how offender profiles are interpreted.…”
Section: Discussionmentioning
confidence: 92%
“…Some researchers attribute the considerable acceptance rate of high base-rate feedback to human gullibility, whereas others note the importance of factors such as social desirability, situational insecurity, and interpreter prestige (PiperTerry & Downey, 1998). Furthermore, Snyder, Larsen, and Bloom's (1976) results suggested that people are more inclined to accept a bogus personality description when it is believed to be based on a psychological assessment procedure rather than an alternate technique such as astrology, although in that study, differences in the degrees of acceptance were marginal.…”
Section: Finding Meaning In Ambiguous Informationmentioning
confidence: 99%